Optimalisasi Guru PAI Dalam Penggunaan Media Audio Visual Untuk Meningkatkan Minat Belajar Siswa SMP Kota Batam - Afi Parnawi; Sumianti Sumianti (Journal on Education, 2023)
This study aims to determine the efforts made by teachers in using audio-visual media to increase the learning interest of class IX students Batam City, as well as to determine the supporting and inhibiting factors. This research is a qualitative research using observation, interviews and documentation to obtain data. Furthermore, the data will be analyzed descriptively. The results of the study show that the efforts made by the teacher in using audio-visual media to increase student interest in learning are by displaying learning videos, developing subject matter during material delivery, and providing conclusions about the learning videos that are displayed, and always providing motivation so that students always have an interest and enthusiasm for learning. The effort is stated to be effective in its use. The supporting factors are the availability of school facilities, students' interest in participating in learning, and the increasingly sophisticated technology. And the inhibiting factors are changes in student conditions, inadequate classrooms, and limited facilities.